Optimizing cyanobacterial product synthesis: Meeting the challenges - Zavřel, Tomáš; Červený, Jan; Knoop, Henning; Steuer, Ralf (Bioengineered, 2016)
The synthesis of renewable bioproducts using photosynthetic microorganisms holds great promise. Sustainable industrial applications, however, are still scarce and the true limits of phototrophic production remain unknown. One of the limitations of further progress is our insufficient understanding of the quantitative changes in photoautotrophic metabolism that occur during growth in dynamic environments. We argue that a proper evaluation of the intra- and extracellular factors that limit phototrophic production requires the use of highly-controlled cultivation in photobioreactors, coupled to real-time analysis of production parameters and their evaluation by predictive computational models. In this addendum, we discuss the importance and challenges of systems biology approaches for the optimization of renewable biofuels production. As a case study, we present the utilization of a state-of-the-art experimental setup together with a stoichiometric computational model of cyanobacterial metabolism for quantitative evaluation of ethylene production by a recombinant cyanobacterium Synechocystis sp. PCC 6803.
Keywords: počítačová simulace; Ethylenes; Systems Biology; cyanobacteria; genome-scale models (GSM); systems biology; fotosyntéza; Computer Simulation; Biofuels; ethylene; biofuels; Synechocystis; Metabolic Engineering; MIMS; Photosynthesis; systémová biologie; ethyleny; photobioreactors; biotechnology; biopaliva; metabolické inženýrství